Pengembangan Bahan Ajar Interaktif Berbasis Canva Mata Pelajaran IPAS Model Addie di SDN Daleman 2 - Azizah, Nurul; Fatirul, Achmad Noor; Harwanto, Harwanto (MODELING: Jurnal Program Studi PGMI, 2024)
With the development of technology and understanding of how humans learn throughout life that places education as a dynamic and continuous process and involves all aspects of life, learning innovation will be an integral part in improving the education system. Quality education is a learning designed to provide learning experiences to students that not only convey learning facts and concepts, but involves developing skills, attitudes, and building character and values that can support the growth of students as knowledgeable, creative and responsible individuals in society (Habaridota, 2023). In today's digital and technological era, the use of teaching materials is an important part of the learning process to achieve the expected competencies and increase effectiveness and motivation in learning (Wahyudi, 2022) (Novayana et al., 2021). gaps in the use of teaching materials used in the learning process in conventional science subjects so that learning is still monotonous centered on students, then interactive teaching materials are indispensable in helping the involvement of students in the learning process (Puspasari, 2022). Based on the gaps that arise in the learning process, researchers will develop canva-based teaching materials to overcome problems in science subjects related to providing interactive teaching material references that can be used in the learning process to encourage students to optimally involve students in the grade 4 science learning process at SDN Daleman 2 Galis District. In research on the development of Canva-based interactive teaching materials refers to the ADDIE model. Systematically prepared based on the independent curriculum in the grade 4 basic education unit at SDN Daleman 2 Galis District, which is adjusted to the characteristics of the learning material and the characteristics of students.